2021
DOI: 10.1016/j.jgr.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ginsenoside compound K loaded ionically cross-linked carboxymethyl chitosan–calcium nanoparticles and its cytotoxic potential against prostate cancer cells

Abstract: Backgroud Ginsenoside compound K (GK) is a major metabolite of protopanaxadiol-type ginsenosides and has remarkable anticancer activities in vitro and in vivo . This work used an ionic cross-linking method to entrap GK within O-carboxymethyl chitosan (OCMC) nanoparticles (Nps) to form GK-loaded OCMC Nps (GK–OCMC Nps), which enhance the aqueous solubility and stability of GK. Methods The GK–OCMC Nps were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In a recent comparative study on CK and CK within OCMC NPs showed that the later had higher water solubility and membrane permeability [ 42 ]. Similarly, a recent study found that CK-loaded with A54-PEG-DA-OCMC, known as APD-CK micelles, enhanced the delivery of CK.…”
Section: Pharmacokinetics Metabolism and Safety Of Compound Kmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent comparative study on CK and CK within OCMC NPs showed that the later had higher water solubility and membrane permeability [ 42 ]. Similarly, a recent study found that CK-loaded with A54-PEG-DA-OCMC, known as APD-CK micelles, enhanced the delivery of CK.…”
Section: Pharmacokinetics Metabolism and Safety Of Compound Kmentioning
confidence: 99%
“… ↑cytotoxicity for A549 and HT29 compared to CK ↑apoptosis after laser treatment in AGS [ 40 ] CK + chitosan NPs In vitro HepG2 cells CK and CK-NPs (3.125, 6.25, 12.5, 25, and 30 μg/mL), 24 h At 30 μg/mL, the apoptotic cell percentage, CK (39.02 ± 0.42%) and CK-NPs (47.57 ± 1.65%) [ 41 ] GK-OCMC NPs In vitro PC3 cells CK and GK-OCMC NPs (30 μg/mL) ↑ apoptosis by GK-OCMC treatment ↑ levels of caspase-3 (29.93%) and caspase-9 (20.78%) compared to GK treatment. [ 42 ] APD-CK micelles In vitro HepG2 and Huh-7 cells CK (30, 20, 10, 5, and 2.5 μg/mL), 24 h and 48 h Time-dependent and dose-dependent cytotoxic effects of APD-CK ↑expressions of PARP, caspase-3, and -9 in HepG2 cells by APD-CK micelles [ 43 ] Parthenolide/ CK tLyp-1 liposomes In vivo Nude mice 5 mg/kg, 24 h Strong tumor inhibition with parthenolide/ CK tLyp-1 liposomes than combined [ 91 ] In vitro A549 Parthenolide (1.5 µg/mL) + CK (30 µg/mL) in 5:1 ratio ↑ mitochondrial apoptosis: CK (8.2%), parthenolide (11.8%), CK+ parthenolide (34.7%), Parthenolide/ CK tLyp-1 liposomes (56.7%) ↑ROS levels: CK (3.7%), parthenolide (5.8%), CK+ parthenolide (24.6%), Parthenolide/ CK tLyp-1 liposomes (28.7 %) Marked structural changes in mitochondria and impaired mitochondrial membrane potential …”
Section: Health-promoting Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A new study discovered that CK-loaded ionically crosslinked carboxymethyl chitosan-calcium nanoparticles enhance the water solubility and permeability, thereby increasing the cytotoxicity and cellular uptake of CK toward prostate cancer cells (Zhang et al, 2021).…”
Section: Mechanisms Key Indicators Referencementioning
confidence: 99%
“…17,18 At present, research on the construction of nanodrug delivery systems for the delivery of ginsenosides (such as ginsenoside compound K) has been reported. 19 However, the results of clinical trials show that the traditional polymer nanocarriers may not be able to achieve the programmed release of drugs in pathological changes, resulting in multiple drug resistance of cells and reduced efficacy. 20 Meanwhile, because of the simple physical encapsulation and the instability of the carrier in vivo, the drug can easily leak out of the nanocarrier in the systemic circulation, which leads to serious side effects.…”
Section: ■ Introductionmentioning
confidence: 99%